In situ synthesis of supported metal nanocatalysts through heterogeneous doping - No Woo Kwak (Nature Portfolio, 2018)
Supported metal nanoparticles hold great promise for many fields, including catalysis and renewable energy. Here the authors report a novel methodology for the in-situ growth of architecturally tailored, regenerative metal nanocatalysts that is applicable to a wide range of materials.